2014
DOI: 10.3329/jsr.v6i2.16994
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Some Mixed Ligand Complexes of Zn(II) with 4, 4´- Bipyridine: Anti-inflammatory and Analgesic Activities of these Complexes

Abstract: The mixed ligand complexes of Zn(II) with 4,4-bipyridine and some organic acids or amino acids were prepared in the solid form and characterized by elemental analysis, conductivity, magnetic moment measurement, IR, 1 H-NMR, 13 C-NMR and FAB + mass studies. To study anti-inflammatory and analgesic activities of these complexes, some Swiss albino mice of 5-7 weeks old were taken. One dose of the test compounds of 10 mg/kg was selected throughout the research work. The anti-inflammatory activity of the test compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, Inorganic elements play crucial role in biological and biological medical processes, and it is evident that many organic compounds used in medicine do not have a purely organic mode of action, some of them are activated or bio transformed by metal ions metabolism. Many drugs possess modified toxicological and pharmacological properties in the form of metal complex and probably Schiff bases are versatile C=N (imine) containing compounds possessing broad spectrum of biological activity and incorporation of metals in the form of complexes showed some degree of antibacterial, antifungal, antitumor, anticancer and anti-inflammatory activity [4][5][6][7][8]. In vivo studies have indicated that some biologically active compounds may become more carcinostatic and bacteriostatic upon chelation [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Inorganic elements play crucial role in biological and biological medical processes, and it is evident that many organic compounds used in medicine do not have a purely organic mode of action, some of them are activated or bio transformed by metal ions metabolism. Many drugs possess modified toxicological and pharmacological properties in the form of metal complex and probably Schiff bases are versatile C=N (imine) containing compounds possessing broad spectrum of biological activity and incorporation of metals in the form of complexes showed some degree of antibacterial, antifungal, antitumor, anticancer and anti-inflammatory activity [4][5][6][7][8]. In vivo studies have indicated that some biologically active compounds may become more carcinostatic and bacteriostatic upon chelation [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases and its complexes are used as pigments and dyes, catalysts, intermediate in organic synthesis, and as a polymer stabilizer [3]. Schiff bases are versatile -C=N (imine) containing compounds possessing broad spectrum of biological activity and the incorporation of metals in the form of complexes showed some degree of antibacterial, antifungal, antitumor, anticancer and anti-inflammatory activity [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%